ANALISIS PERBANDINGAN PERFORMANSI KEKUATAN DAN KINERJA ALGORITMA RIVEST SHAMIR ADLEMAN (RSA) DAN ELLIPTIC CURVE CRYPTOGRAPHY (ECC) PADA FLUTTER - Pratama, Yoga; Hansen, Jerry; Sutabri, Tata (JURSIMA, 2022)
Technological changes and advances have made human life easier. Along with this, the crime factor in technology is also becoming more open, for example data theft, or other technological crimes that threaten the pace of technology itself. For this reason, handling and prevention are needed in anticipating technological crimes, one of which is cryptography. Cryptography is an important science in the digital world which is intended to protect data and information from unauthorized access. RSA (Rivest-Shamir-Adleman) and ECC (Elliptic Curve Cryptography) are two examples of cryptographic algorithms used to secure data. This study aims to compare the power and performance of the RSA and ECC algorithms. The implementation of these two algorithms is carried out in the Flutter environment which will be evaluated, including aspects of security and speed of data encryption and decryption. The results of this study are intended to add a deeper understanding and provide an overview of these two cryptographic algorithms in protecting data in an information technology system.